2017
DOI: 10.1093/ije/dyx137
|View full text |Cite
|
Sign up to set email alerts
|

Domain-specific physical activity and sedentary behaviour in relation to colon and rectal cancer risk: a systematic review and meta-analysis

Abstract: In addition to increasing occupational and recreational physical activity, promoting physical activity during transport and reducing sedentary behaviour in the workplace may also be useful colorectal cancer prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 86 publications
6
48
3
4
Order By: Relevance
“…By applying two-sample MR, we observed a causal effect of accelerometer-based PA on CRC and a suggestive association between self-reported PA and CRC [14]. The MR results for both types of PA were similar to the results from the meta-analyses of observational studies [5].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…By applying two-sample MR, we observed a causal effect of accelerometer-based PA on CRC and a suggestive association between self-reported PA and CRC [14]. The MR results for both types of PA were similar to the results from the meta-analyses of observational studies [5].…”
Section: Discussionsupporting
confidence: 75%
“…The self-reported PA related variants explained approximately 0.03% of PA. We fixed the type I error at α<0.05 and applied an assumed true effect estimate of OR=0.80 per 1 SD increase of the PA time. This assumed true effect estimate was obtained from the World Cancer Research Fund meta-analysis of cohort and case-control studies of PA on CRC risk [5]. Power was estimated to be less than 0.10 and F statistic was 14.22 for a sample size of 31 197 CRC cases and 61 770 controls.…”
Section: Power Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…1.04, 1.68) (17), although time spent using computers (excluding using a computer at work) was not associated with colorectal cancer risk in the UK Biobank cohort (17). The findings of a 2017 metaanalysis including six studies also demonstrated significant associations between the highest compared with the lowest levels of occupational sedentary behaviour, and risk of colon cancer (pooled RRs 1.44, 95% CI: 1.28, 1.62) (18). On the other hand, there was little evidence of an association between sedentary behaviour and rectal cancer risk (18).…”
Section: Introductionmentioning
confidence: 92%
“…In contrast, higher levels of TV viewing time were associated with a greater risk of colon cancer in the same study population (HR for ≥5 hours per day vs ≤ 1 hour per day = 1.32, 95% CI: 1.04, 1.68) (17), although time spent using computers (excluding using a computer at work) was not associated with colorectal cancer risk in the UK Biobank cohort (17). The findings of a 2017 meta-analysis including six studies also demonstrated significant associations between the highest compared with the lowest levels of occupational sedentary behaviour, and risk of colon cancer (pooled RRs 1.44, 95% CI: 1.28, 1.62) (18). On the other hand, there was little evidence of an association between sedentary behaviour and rectal cancer risk (18).…”
Section: Introductionmentioning
confidence: 92%